Mitophagy-associated programmed neuronal death and neuroinflammation - Zhu, Yanlin; Zhang, Jianning; Deng, Quanjun; Chen, Xin (Frontiers in Immunology, 2024)
Mitochondria are crucial organelles that play a central role in cellular metabolism and programmed cell death in eukaryotic cells. Mitochondrial autophagy (mitophagy) is a selective process where damaged mitochondria are encapsulated and degraded through autophagic mechanisms, ensuring the maintenance of both mitochondrial and cellular homeostasis. Excessive programmed cell death in neurons can result in functional impairments following cerebral ischemia and trauma, as well as in chronic neurodegenerative diseases, leading to irreversible declines in motor and cognitive functions. Neuroinflammation, an inflammatory response of the central nervous system to factors disrupting homeostasis, is a common feature across various neurological events, including ischemic, infectious, traumatic, and neurodegenerative conditions.Emerging research suggests that regulating autophagy may offer a promising therapeutic avenue for treating certain neurological diseases. Furthermore, existing literature indicates that various small molecule autophagy regulators have been tested in animal models and are linked to neurological disease outcomes. This review explores the role of mitophagy in programmed neuronal death and its connection to neuroinflammation.